Self-repairs as right node raising constructions - Husband, E (Elsevier, 2015)
In normal everyday speech, speakers occasionally become disfluent, mis-speak, and then correct their utterances mid-sentence. While these errors and repairs seem to be a natural case of language performance, language competence also plays an intimate role in shaping their ultimate form. Drawing on and extending insights from Levelt, 1983 and Levelt, 1989, this paper argues that self-repairs are a species of right node raising. I demonstrate that self-repairs share many of the properties of right node raising constructions, with the resumption behaving like the shared material of right node raising. I also suggest that self-repairs may illuminate the current theoretical bind seen in the analysis of right node raising by supporting recent proposals that favor a sparse representation for right node raising constructions.